Immunoenhancement activity of Bletilla striata polysaccharide through MAPK and NF-κB signalling pathways in vivo and in vitro. (17th November 2022) - Niu, Xiaofeng; Yu, Jiabao; Huang, Qiuxia; Yu, Jinjin; Yang, Yajie; Song, Huixin; Liu, Yang; Xiao, Xin; Cui, Langjun; Li, Weifeng
Abstract: Bletilla striata (Thunb.) Reichb.f., is a traditional Chinese medicine, and the Bletilla striata polysaccharide (BSP) is one of the principal components extracted from Bletilla striata with various biological activities. Previous studies have shown that many natural polysaccharides have significant immunomodulatory activities. However, as a plant polysaccharide, the research of BSP on immunomodulatory activities is limited. In this study, we aim to investigate the immunomodulatory effect of BSP in vivo and further explore its underlying mechanism in vitro . In vivo, a cyclophosphamide (CTX)-induced immunosuppression mice mode was established by intraperitoneal injection of CTX, and the immune-enhancing effect of BSP (25, 50 and 100 mg/kg) on immunosuppressed mice were evaluated. The result indicated that BSP could significantly improve the immune organ index and the content of immunoglobulin, TNF-α and IL-4 in serum. It was also found that BSP could clearly ameliorate the spleen damage induced by CTX. Meanwhile, the result showed that BSP could not only improve the proliferation of splenocytes, but also activate the lactate dehydrogenase (LDH) and acid phosphatase (ACP) in mouse spleen tissue. In vitro, potential mechanism was further revealed in macrophages. The result supported that BSP could activate macrophages with high phagocytic ability, and induce macrophages to secrete cytokines. Finally, it revealed that activation of NF-κB and MAPK signalling pathway should be the underlying mechanism of the immunoenhancment of BSP.